Donde me escondo? = Where am I hiding? - Zagarenski, Pamela (Boston, MA : Houghton Mifflin Co., 2005)
Prepositions are introduced through a mischievous elephant who hides in unusual places.
Cover title.
Keywords: Spanish language -- Glossaries, vocabularies, etc. -- Juvenile literature; Elephants -- Juvenile literature; Hide-and-seek -- Juvenile literature; Vocabulary -- Juvenile literature; Español -- Glosarios, vocabularios, etc. -- Literatura juvenil; Vocabulario -- Literatura juvenil; Elefantes -- Literatura juvenil; Escondite -- Literatura juvenil